Accounting for Microdosing Classic Psychedelics. (January 2020) - Beaton, Blake; Copes, Heith; Webb, Megan; Hochstetler, Andy; Hendricks, Peter S.
Microdosing classic psychedelics (e.g., LSD [lysergic acid diethylamide] and psilocybin) is the practice of taking small amounts of these substances to bring about various positive life changes. Little is known about the subjective experiences and perceptions of those who engage in the practice. Accordingly, we use the sociology of accounts as a theoretical framework to explore the ways that those who microdose excuse or justify their practice. Using data from semistructured interviews with 30 people who had microdosed, we find that none provided excuses for their microdosing, but all offered one or more justifications. When discussing their microdosing, participants emphasized six key justifications: denial of injury, self-sustaining, self-fulfillment, appeal to normality, appeal to loyalties, and knowledgeableness. Findings provide insights into the subjective experiences of those who microdose, including the ways that they attempt to align their actions with societal expectations.